Comparison of Intrathecal Bupivacaine Versus Bupivacaine plus Dexmedetomidine for Postoperative Pain Relief in Terms of Quality and Duration - Afzal, Zainab; Rao, Zahid Akhtar; Sameuddin, Syed; Khalid, Muhammad; Sultan, Muhsan; Saqib, Najm Us (Pakistan Armed Forces Medical Journal, 2025)
Objective: To measure the clinical efficacy of intrathecal Bupivacaine alone versus intrathecal Bupivacaine plus Dexmedetomidine on postoperative pain alleviation in terms of quality and duration in women undergoing C-sectionStudy Design: Randomized controlled trial, (Iranian Clinical Trial Registry: 76165)Place and Duration of Study: Department of Anaesthesiology, PAF Hospital (Faisal), Karachi Pakistan from Sep, 2023 to Feb 2024.Methodology: After registration with trial registry (ICTR) and ethical approval, this randomized controlled trial was performed in Anaesthesia department of PAF Hospital (Faisal), Karachi. Intrathecal Dexmedetomidine was given as an adjuvant to Bupivacaine in 33 gravid ladies (Group A) after randomization. Group A and Group B patients were followed for 24 hours post-operatively to assess duration and quality of analgesia. Statistical significance was compared between both study Groups.Results: At twenty-four hours of time lapse, 2(6.1%) Group A patients had mild pain, 24(72.7%) had moderate pain and 7(21.2%) had severe pain compared to 7(21.2%) Group B patients who had moderate pain and 26(78.8%) had severe pain with p-value